A systematic review of the use of rifaximin for Clostridium difficile infections. (February 2019) - Ng, Qin Xiang; Loke, Wayren; Foo, Nadine Xinhui; Mo, Yin; Yeo, Wee-Song; Soh, Alex Yu Sen
Abstract: Clostridium difficile infection (CDI) is an increasingly common occurrence in the hospital setting, and it is associated with significant morbidity and mortality. In vitro studies have found that rifaximin, a nonabsorbable rifamycin antibiotic, displays potent antimicrobial activity against C. difficile . This systematic review thus aimed to examine the clinical role of rifaximin in CDI. Using the keywords [clostridium OR difficile OR colitis] AND [rifaximin OR xifaxan OR rifagut], a preliminary search on the PubMed, EMBASE, Medline, Clinicaltrials.gov and Google Scholar databases yielded 6210 papers published in English between 1-Jan-1988 and 1-Jul-2018. A total of eight clinical trials were systematically reviewed. Of these, only two were randomized, controlled trials. In the treatment of mild-moderate CDI, rifaximin is a viable alternative to existing therapies (metronidazole or vancomycin). More importantly, rifaximin has a potential role in conjunction with other therapies, showing to be efficacious in reducing the rate of CDI recurrence. However, clinical studies have reported a resistance rate in the range of 29.1–48.9%, with a geographical variance in the distribution of rifaximin-resistant C. difficile strains. With its unique eubiotic properties and positive modulation of the gut flora, rifaximin has a potential therapeutic role in the management of CDI, especially in CDI recurrences. As there is a paucity of randomized, controlled trials to support its use, studies with larger and more diverse populations should be conducted before the efficacy of rifaximin can be conclusively stated. Rifaximin is also a relatively expensive antimicrobial, further studies should include cost-benefit analyses. Highlights: This is the first systematic review to examine the use of rifaximin for C. difficile infections (CDI). 8 clinical trials were systematically reviewed. Rifaximin is a viable alternative for CDI. It also shows efficacy in reducing the recurrence of CDI. Further detailed trials and cost-benefit analyses are warranted.